EVALUASI KEBERHASILAN INSEMINASI BUATAN (IB) PROGRAM UPSUS SIWAB DI KABUPATEN BERAU (Jurnal Peternakan Lingkungan Tropis, 2021)
To achieve this self-sufficiency in meat, the government has made a number of policies. One of them is to encourage population growth of cattle and buffalo through the Special Efforts for Mandatory Pregnant Cows (Upsus SIWAB). This research was conducted to determine the success of artificial insemination of the SIWAB Upsus program in Berau Regency. This research was conducted in Gunung Tabur and Teluk Bayur Districts, Berau Regency in January 2020 and the Animal Reproduction and Breeding Laboratory. Data collection was carried out using the interview method with questionnaire tools. Secondary data were obtained from the Agriculture and Livestock Service Office of Berau Regency and the inseminator. The variables measured were artificial insemination including S / C, CR and CI, pregnancy, and birth. The research data were analyzed using descriptive analysis, t-test and regression analysis at the 95% confidence level. The results showed that in Gunung Tabur District the average S / C value was 1-2 times, the average CR value was 75%, CI was ideal category because the area reached an average of 12-13 months. Meanwhile, in Teluk Bayur Subdistrict, the average S / C value was below 3 times, CR 70%, the average CI was 14 months. The success of the artificial insemination of the SIWAB Upsus program in Berau Regency is quite good, it can be seen from the S / C, CR and CI in Gunung Tabur and Teluk Bayur Districts; in Gunung Tabur District, Servis Per Conception (S/C) is very good which on average shows less than 3 times the insemination, Conseption Rate (CR) is very good because it is 75%, while the Calving Interval (CI) is the ideal category because the CI reaches an average of 12-13 months. Whereas in Teluk Bayur District, the Service Per Conception (S / C) rate is very good because the average shows below 3 times the insemination, Conseption Rate (CR) is also good because it is 70%, while the Calving Interval (CI) is not ideal because of its high Cl which reached an average of 14 months.
Keywords: Array; Array; Array